Chronic complex patients pathway implementation: the devil is in the details - Zabala Rementeria, Joseba Igor (International journal of integrated care, 2025)
Rationale: The great challenge for health systems is to scale up care processes that have been locally successful. These deployments are subject to a large number of conditioning factors that often mean that the achievements are not reached as they were originally planned. In the Basque Country and within the framework of the health transformation carried out since the 2010s, we have made progress in adapting the system to the enormous challenge of chronicity, emphasizing the framework of integrated care as a response to it. Within this framework, the deployment of major care routes such as the complex chronic patient takes on special relevance. This patient consumes up to 50% of healthcare resources, but as we have said, there are many imponderables to which these deployments are subject. In order to address this we have proposed a new collaborative management methodology working out the details that will help in changing the organizational model for complex patients Objectives: Review of the corporate multimorbid care pathway. Selection of 3 process and result indicators Monitoring and evaluation of achievements Methodology: Two working groups have been sorted to review the care pathway in its transit through primary care and hospital care. A scorecard has been designed with only 3 indicators, collaborative clinical record review CCRR, Shared care plan (SCP) and readmissions < 30days. These objectives have been communicated to all the organizations through virtual sessions and visits to the 13 Integrated care organizations (ICO). Results: These dynamics have ensured that the implementation effort has been shared by all the organizations and clinical professionals. the care pathway has been revisited and adjusted to the current situation. The central governance and the ICO leadership have boosted  the process possitevely. Professionals have felt that they are key participants in the process As can be seen in the results (three cuts carried out up to September 30), the three indicators have been evolving positively.   Indicator/dateMarchMay     September    October CCRR       22,41%    28,45%    29,93%      35,20% SCP         27,85%30,70%   43,22%       51,26% Readmissions  < 30 days15,79%15,01%    14,70%       14,61%   Considerations and limitations: Beyond the great achievements that often omit the details in the implementation processes on a corporate scale, in this case we have focused on three basic indicators, 2 of processes and 1 of results, and we have begun to build from there, making clinical professionals see that by carrying out some basic dynamics we can achieve important impacts on results. One of the strengths of this dynamic of the details is that if we manage to advance uniformly throughout the health system, this will have a driving force on the rest of the routes for chronic patients, especially. The engagement os professioanls and managers has been key for these results. The limitation of this dynamic is that it is still a top-down process on the one hand and that patient participation has been scarce on the other hand.